2016
DOI: 10.1590/s1679-45082016ao3729
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of knowledge about oral cancer among undergraduate dental students

Abstract: Objective:To evaluate and compare the knowledge of dental undergraduate students about oral cancer.Methods:The students were divided into two groups according to semester attended in the undergraduate course: Group A, the first semester; and Group B, seventh semester. They were asked to answer a questionnaire about epidemiology, risk factors, clinical aspects, therapeutic solutions and oral self-examination. For statistical analysis, the Fisher's exact test, the Cochran's G test and Kendall's concordance test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 14 publications
(24 reference statements)
4
3
0
7
Order By: Relevance
“…Tobacco use and alcohol abuse have been identified as prominent aetiologies for oral cancer 4,[17][18][19]20 . Both groups in the present study were aware that these two parameters are positive risk factors, but students who had studied oral medicine were more certain of these factors, which is concordant with the results of previous studies 21,22 .…”
Section: Discussionsupporting
confidence: 92%
“…Tobacco use and alcohol abuse have been identified as prominent aetiologies for oral cancer 4,[17][18][19]20 . Both groups in the present study were aware that these two parameters are positive risk factors, but students who had studied oral medicine were more certain of these factors, which is concordant with the results of previous studies 21,22 .…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the average knowledge of OC and its risk factors among last year students, interns and faculty members is at a moderate level; 20.2 ± 3.6, with no significant difference between them. The findings of the present study are in line with findings reported in the literature in regard to dental-students’ and dentists’ knowledge of diagnostics, clinical aspects, risk factors and prevention of OC ( 22 - 24 ).…”
Section: Discussionsupporting
confidence: 91%
“…In a study done by Samara Ribeiro da Silva 9 found that than in the first semester in the subsequent semesters the awareness was higher, this finding about the knowledge for oral cancers was similar to our study.…”
Section: Discussionsupporting
confidence: 92%
“…In a study done by Samara Ribeiro da Silva 9 Nicotera G, 10 Canto MT 11 found that the awareness of ethanol consumption and smoking as the risk factors was well known, this finding about the knowledge for oral cancers was similar to our study.…”
Section: Discussionsupporting
confidence: 90%